2023
DOI: 10.1002/14651858.cd009365.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise therapy for treatment of acute non-specific low back pain

Wilhelmina IJzelenberg,
Teddy Oosterhuis,
Jill A Hayden
et al.

Abstract: Exercise therapy for treatment of acute non-specific low back pain (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 102 publications
0
1
0
1
Order By: Relevance
“…Four systematic reviews included 32 RCTs ( n = 2628), three RCTs ( n = 197), nine RCTs ( n = 451), and 12 RCTs ( n = 848), respectively. 2730 These systematic reviews showed: (1) there were no clinically important differences between motor control and spinal manipulative therapy for pain in short term and for disability in short term and long term; (2) there were no clinically important differences between motor control and other forms of exercise for pain at short or intermediate term and for disability at intermediate term or long term follow-up; (3) addition of motor control exercise to medical management does not provide clinically important improvement for pain or disability at short-term follow-up; (4) motor control exercise is no better than sham and no treatment for pain and functional status in short term (Level of Evidence I). One systematic review 18 from the American Physical Therapy Association recommended that physical therapists use motor control exercise (trunk muscle activation exercise) for patients with acute LBP (Level of Evidence I).…”
Section: Resultsmentioning
confidence: 99%
“…Four systematic reviews included 32 RCTs ( n = 2628), three RCTs ( n = 197), nine RCTs ( n = 451), and 12 RCTs ( n = 848), respectively. 2730 These systematic reviews showed: (1) there were no clinically important differences between motor control and spinal manipulative therapy for pain in short term and for disability in short term and long term; (2) there were no clinically important differences between motor control and other forms of exercise for pain at short or intermediate term and for disability at intermediate term or long term follow-up; (3) addition of motor control exercise to medical management does not provide clinically important improvement for pain or disability at short-term follow-up; (4) motor control exercise is no better than sham and no treatment for pain and functional status in short term (Level of Evidence I). One systematic review 18 from the American Physical Therapy Association recommended that physical therapists use motor control exercise (trunk muscle activation exercise) for patients with acute LBP (Level of Evidence I).…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23] -und folglich auch nicht die damit verglichenen. Vielen physiotherapeutischen Behandlungsformen mangelt es an wissenschaftlicher Evidenz, wie der Faszientherapie [24], der Triggerpunktbehandlung [25,26], Übungen zur Bewegungskontrolle [27][28][29] und der aktiven Übungstherapie bei akuten [30] und chronischen unteren Rückenschmerzen (LBP) [31]. Ebenso macht es keinen Unterschied, ob wir beispielsweise nach einem HWS-Beschleunigungstrauma wenig oder viel behandeln [32][33][34].…”
Section: Msk-tag Beim Physiokongressunclassified